2010
DOI: 10.1029/2009jd013241
|View full text |Cite
|
Sign up to set email alerts
|

Three‐dimensional charge structure of a mountain thunderstorm

Abstract: Lightning charge transport is analyzed for a thunderstorm which occurred on 18 August 2004 near Langmuir Laboratory in New Mexico. The analysis employs wide band measurements of the electric field by a balloon‐borne electric field sonde or Esonde, simultaneous Lightning Mapping Array measurements of VHF pulses emitted during lightning breakdown, and Next Generation Weather Radar data. The thunderstorm was composed of two principal updrafts. In the stronger updraft the positively charged particles reached altit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 41 publications
2
13
0
Order By: Relevance
“…Stronger updrafts would be expected in the convective region of the storm. Hager et al [] also found the charge regions to decrease in altitude sharply immediately outside of the updrafts followed by a linear rate of descent of around 1 to 2 km in altitude per 10 km in horizontal distance which is similar to what we observed. On 17 July 2012, it is possible that as the storm progressed from south to north, the charge regions behind the most intense convection descended in altitude, with the greatest descent being the farthest from the convective region so that the oldest and farthest part of the storm had the most charge descent.…”
Section: Summary and Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Stronger updrafts would be expected in the convective region of the storm. Hager et al [] also found the charge regions to decrease in altitude sharply immediately outside of the updrafts followed by a linear rate of descent of around 1 to 2 km in altitude per 10 km in horizontal distance which is similar to what we observed. On 17 July 2012, it is possible that as the storm progressed from south to north, the charge regions behind the most intense convection descended in altitude, with the greatest descent being the farthest from the convective region so that the oldest and farthest part of the storm had the most charge descent.…”
Section: Summary and Discussionmentioning
confidence: 97%
“…The relative locations of the inferred charge regions in the convective and stratiform regions on 17 July 2012 are consistent with the observations of Stolzenburg et al [1998a] and Hager et al [2010] who found both the negative and positive charge regions to be located at higher altitudes in regions containing stronger updrafts. Stronger updrafts would be expected in the convective region of the storm.…”
Section: 1002/2014jd022139mentioning
confidence: 99%
“…Outside of the updraft regions and in regions with more horizontal transport of existing hydrometeors, many more charge layers have been observed especially in organized convection such as supercells (Bruning et al, ; Lang et al, ; MacGorman et al, ) or mesoscale convective systems (Stolzenburg et al, ). In less organized convection, such as in this study, the more simplistic vertical motions, advection, and sedimentation cause the primary charge layers to slope downward with distance from the updraft (Hager et al, ). Understanding storm polarity of such simple storms is a crucial foundation for understanding thunderstorm charge generation in more complex storms.…”
Section: Introductionmentioning
confidence: 85%
“…For this purpose we assumed a single acceleration region in the thundercloud with the vertical length and horizontal one of Z ¼ 500 m or 1000 m and L ¼ 600 m [7], respectively. In reality, a positive or a negative charge layer of thunderclouds may consist of multicells (e.g., [45]) to form several acceleration areas therein. Thus, the single acceleration region is a simple assumption to consider individual particle accelerations.…”
Section: Avalanche Multiplication Factormentioning
confidence: 99%